2011
DOI: 10.5194/acp-11-9865-2011
|View full text |Cite
|
Sign up to set email alerts
|

Zonal asymmetries in middle atmospheric ozone and water vapour derived from Odin satellite data 2001–2010

Abstract: Abstract. Stationary wave patterns in middle atmospheric ozone (O 3 ) and water vapour (H 2 O) are an important factor in the atmospheric circulation, but there is a strong gap in diagnosing and understanding their configuration and origin. Based on Odin satellite data from 2001 to 2010 we investigate the stationary wave patterns in O 3 and H 2 O as indicated by the seasonal long-term means of the zonally asymmetric components

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 50 publications
7
57
0
Order By: Relevance
“…This differs from the asymmetry axis about 0 • -180 • E in the 100-hPa temperatures in Fig. 1 because of westward tilt of the QSW phase with altitude (Randel, 1988;Gabriel et al, 2011). Temperature fields (not shown) indicate also that the TOC maximum between 90 • E and 180 • E in Fig.…”
Section: Zonal Asymmetrymentioning
confidence: 95%
See 2 more Smart Citations
“…This differs from the asymmetry axis about 0 • -180 • E in the 100-hPa temperatures in Fig. 1 because of westward tilt of the QSW phase with altitude (Randel, 1988;Gabriel et al, 2011). Temperature fields (not shown) indicate also that the TOC maximum between 90 • E and 180 • E in Fig.…”
Section: Zonal Asymmetrymentioning
confidence: 95%
“…The largest changes in the ozone field in 2002 occur between about 90 • E and 240 • E (Fig. 6b) as a result of the maximum ozone accumulation due to the BDC which tend to be zonally asymmetric in the SH stratosphere (Salby and Callaghan, 2004;Sato et al, 2009;Gabriel et al, 2011). The TOC minimum between about 0 • E and 60 • W (Fig.…”
Section: Zonal Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many previous studies have demonstrated the important role of planetary waves in modulating ZAO variations (e.g. Peters and Entzian 1999;Peters et al 2008;Efstathiou et al 2003;Hio and Yoden 2004;Grytsai et al 2005;Gabriel et al 2011;Ialongo et al 2012;Zhang et al 2015) and have proposed that the planetary waves of tropospheric origin could affect TCO through tropopause height modulations and stratosphere-troposphere exchange processes. Nevertheless, whether and to what extent planetary wave changes exert an influence on the zonally asymmetric TCO trend in the past 30 years remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we will analyze ZAO variations over the past three decades and diagnose the relative importance of various processes which dominate the zonally asymmetric TCO trend over the whole northern middle latitudes during winter (December-January-February, DJF) when the ZAO structure is more pronounced (Hood and Zaff 1995;Gabriel et al 2011). Data and methods are described in Sect.…”
Section: Introductionmentioning
confidence: 99%